Shadow of a Kaluza-Klein rotating dilaton black hole - Amarilla, Leonardo (2013)
We study the shadow produced by a spinning Kaluza-Klein black hole in Einstein gravity coupled to a Maxwell field and a dilaton. The size and the shape of the shadow depend on the mass, the charge, and the angular momentum. We find that, for fixed values of these parameters, the shadow is slightly larger and less deformed than for its Kerr-Newman counterpart.